Makna Simbol Budaya dalam Tradisi Permainan Masyarakat Gorontalo di Desa Sukamaju, Kecamatan Wonosari, Kabupaten Boalemo: Penelitian - Wirnawati Harun; Ellyana Hinta; La Ode Gusman Nasiru (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
This study aims to identify the forms of cultural symbols, symbolic meanings, and mythic narratives found in the traditional games of the Gorontalo community in Sukamaju Village, Boalemo Regency. The research focuses on understanding these games as a system of signs that reflects local worldviews, social values, and cultural identity. A descriptive qualitative method with a case study design was used, with data collected through observation, in-depth interviews, and documentation of surviving games such as mongawuta, mokainje, mopondi, and mokalari. The analysis employs Roland Barthes’s semiotic theory, which categorizes meaning into denotation, connotation, and myth. The findings show that cultural symbols appear in natural materials used in the games, rules, movement patterns, and social interactions among players. Each game element represents life values, including balance, precision, patience, and cooperation, while also containing mythic narratives that help strengthen cultural id